2021
DOI: 10.3390/mi12111368
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Sintered Mg-Zn Supersaturated Solid Solution with High Corrosion Resistance

Abstract: Solid solutions of Zn as an alloy element in Mg matrixes are expected to show improved corrosion resistance due to the electrode potential being positively shifted. In this study, a supersaturated solid solution of Mg-Zn alloy was achieved using mechanical alloying (MA) combined with laser sintering. In detail, supersaturated solid solution Mg-Zn powders were firstly prepared using MA, as it was able to break through the limit of phase diagram under the action of forced mechanical impact. Then, the alloyed Mg-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…To understand the reason for the supersaturation, we investigated the synthetic methods for supersaturation states in other studies. Previous studies have shown that mechanical alloying, such as high-energy ball milling, is a synthetic method for supersaturated materials [24] , [34] , [35] . In mechanical alloying, to form and maintain supersaturated materials, a supersaturated state is formed by a localized high-temperature and -pressure field and maintained by quenching effects [35] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the reason for the supersaturation, we investigated the synthetic methods for supersaturation states in other studies. Previous studies have shown that mechanical alloying, such as high-energy ball milling, is a synthetic method for supersaturated materials [24] , [34] , [35] . In mechanical alloying, to form and maintain supersaturated materials, a supersaturated state is formed by a localized high-temperature and -pressure field and maintained by quenching effects [35] .…”
Section: Discussionmentioning
confidence: 99%
“…The redox potential of a metal can be adjusted by forming a solid solution with other metals [34] , [35] . Yang et al reported that supersaturated Mg–Zn solid solution, synthesized by mechanical milling and laser sintering, has higher corrosion resistance than metallic Mg [35] , which is attributed to the increase in the redox potential of Mg (−2.37 V SHE ) when Zn (−0.762 V SHE ) is introduced into the Mg matrix [33] , [35] .…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the fact that the released Zn ions exerted a positive role. Zn plays a significant role in the formation, development, mineralization, and maintenance of healthy bones [ 36 , 37 ]. Thus, it was expected that Zn ions released from the Fe/ZnS composites could promote cell growth and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the lack of nanoscale corrosion information, precise and fast mimicking of corrosive environments is another key challenge. Traditionally, corrosion coupon testing and climatic chamber testing are used to investigate general corrosion [ 61 , 62 ]. The former one in the form of measuring the mass loss of specimens requires long exposure periods of several years, while the latter considers only a few environmental factors.…”
Section: Deterioration Of Aluminum Windowsmentioning
confidence: 99%